Occupational Stress Management According to David C. Mohr: Book Review of Stress and Mood Management Program for Individuals with Multiple Sclerosis - Alkhafidhoh, Faizah; Sopingi, Imam; Hidayati, Athi’ (Program Studi Ekonomi Islam, Fakultas Ekonomi, Universitas Hasyim Asy'ari Tebuireng, 2025)
This article presents a book review of